Anti-Violence Education Through Electronic Media and Parent Supervision for Early Childhood in the Perspective of Psychology - Lismanda, Yorita Febry; Dewi, Mutiara Sari; Anggraheni, Ika (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2016)
Children of 4-6 years are in concrete pre-operational stage. Negative Stimulus obtained by a child at that time, forming attitudes of children in the future. TV shows, games, and videos containing violence are form of negative stimulus. KPAI data showed 78.3% of children aged elementary school to senior high school have undertaken such violence. One of the factors is possibly the existence of negative stimulus acquired since early childhood. Based on the presentation, this proceeding discusses alternative methods to overcome violence since children aged 4-6 years from the perspective of psychology. The approach used in this proceeding is a qualitative approach. Data was taken from the fact of a numbers violence that have been undertaken by children, TV shows, games, and videos containing elements of violence, stages of child development, and the impact of the show. The data was retrieved through library research of several references that were analyzed and the results were presented descriptively. Based on the data obtained, the conclusion of the proceeding is: the causing factor that lead children to become abusers come from TVâs program containing violence and imitated since early childhood. How to cope with children who commit in violent is by giving TV shows of electronic media (TV, games, videos) containing a lot of educational value and strengthened them with their close relative supervision, especially parents since the children in early age. Keywords: violence aged 4-6 years, electronic media, supervision. Anak usia 4â6 tahun berada pada tahap pra operasional konkrit. Stimulus negatif yang diperoleh anak pada masa itu, membentuk sikap anak di masa yang akan datang. Adanya tontonan Tv, games, dan video yang mengandung tindak kekerasan merupakan bentuk stimulus negatif. Data KPAI menunjukkan 78,3% anak usia MI hingga SMA melakukan kekerasan. Salah satu faktor yang menyebabkan, dimungkinkan adanya stimulus negatif yang diperoleh anak sejak dini. Berdasarkan paparan tersebut, prosiding ini membahas alternatif mengatasi kekerasan sejak anak usia 4â6 tahun dari perspektif psikologi. Pendekatan yang digunakan dalam prosiding ini adalah pendekatan kualitatif. Data berupa fakta banyaknya kekerasan yang dilakukan anak,  tontonan di TV, games, dan video yang mengandung unsur kekerasan, tahapan perkembangan anak, dan dampak dari tontonan. Data tersebut diambil melalui studi pustaka dari beberapa referensi yang  dianalisis  dan hasilnya disampaikan secara deskriptif. Berdasarkan data yang diperoleh, simpulan dari prosiding ini: faktor penyebab anak menjadi pelaku kekerasan berasal dari tontontan yang mengandung tindak kekerasan dan ditiru anak sejak dini. Cara mengatasi anak yang melakukan kekerasan adalah dengan pemberian tontonan pada media elektronik (tv, games, video) yang banyak mengandung nilai edukasi dan diperkuat adanya pengawasan orang dewasa terdekatnya, khususnya orang tua sejak anak dalam usia dini. Kata kunci: kekerasan usia 4-6 tahun, media elektronik, pengawasan.